1992
DOI: 10.1210/endo.130.3.1347008
|View full text |Cite
|
Sign up to set email alerts
|

Pyridostigmine-mediated growth hormone release: evidence for somatostatin involvement.

Abstract: Pyridostigmine (PD), a cholinesterase inhibitor, has been shown to elicit GH release when given alone and to potentiate the GH response to GH-releasing hormone (GHRH) in man. Numerous experiments have indirectly indicated that somatostatin (SS) inhibition is its likely mechanism of action. This study sought to establish the ability of PD to induce GH release in the rat, determine the dose-response relationship, and test the hypothesis that SS inhibition is the method of action. Three experiments were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
1
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
2
18
1
1
Order By: Relevance
“…The increase in plasma GH concentrations would enhance hypothalamic SS tone (and probably reduce concomitantly the activity of GHRH-secreting neurons) (43±47), thus blunting the subsequent responsiveness to GHRH. Supporting this proposition is the ®nding that a cholinergic drug, pyridostigmine, which inhibits SS release (48), given before the second GHRH bolus, reinstates GH responsiveness to the peptide in humans (49,50).…”
Section: Discussionmentioning
confidence: 94%
“…The increase in plasma GH concentrations would enhance hypothalamic SS tone (and probably reduce concomitantly the activity of GHRH-secreting neurons) (43±47), thus blunting the subsequent responsiveness to GHRH. Supporting this proposition is the ®nding that a cholinergic drug, pyridostigmine, which inhibits SS release (48), given before the second GHRH bolus, reinstates GH responsiveness to the peptide in humans (49,50).…”
Section: Discussionmentioning
confidence: 94%
“…Although we did not include the test that demonstrates that PST pretreatment does not increase the TSH response to TRH, we previously had demonstrated that 120mg of PST could not affect TRH-stimulated TSH response (33). Therefore, the comparable TSH responses between Test 2 and 5 exclude the possibility that glucose ingestion suppresses the TRH-induced TSH response after pretreatment with PST.The activation of the cholinergic system inhibits the release of SRIH from the rat hypothalamus in vitro (20) and in vivo (14,28,30) and thereby increases GH secretion. PST, a cholinesterase inhibitor, is known to increase both basal (9,15) and GHRH-induced GH release in man (2,6,8,10,13,19,21).…”
mentioning
confidence: 99%
“…5), the GH response to GHRH after saline infusion appeared to be exaggerated in comparison to the response range usually observed in normal subjects. This observation suggests the existence of two subgroups of acromegalics: one with normal and the other with exaggerated [27] GH response to GHRH. Interestingly, also in the patient with GH hyperresponsiveness to GHRH hydrocortisone inhibited the GH response to GHRH, suggesting similar sensitivity to acute hypercortisolism, and therefore somatostatin in crease, in the two subgroups of acromegalic patients.…”
Section: Discussionmentioning
confidence: 88%